Fourniers gangrene-A case report and literature review - Agarwal, A; Karmacharaya, A; Hirachan, S; Belokar, WK (Journal of College of Medical Sciences-Nepal, 2012)
Fournier’s gangrene(FG) is a rare, necrotising fasciitis of the genitals and perineum with occasional cranial extension to the abdominal wall caused by a mixture of aerobic and anaerobic microorganisms. The complications of this synergistic infection are multiple organ failure and death. Due to the aggressive nature of this condition, early diagnosis is crucial. Treatment involves extensive soft tissue debridement and broad-spectrum antibiotics. Despite appropriate therapy, mortality is high. We report a case of a gentleman who presented with gangrenous and necrotic penile, scrotal and perineal areas. Patient was successfully managed by extensive soft tissue debridement, broad spectrum antibiotics and skin grafting. DOI: http://dx.doi.org/10.3126/jcmsn.v7i3.6713 Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-3, 62-67